Inflammation and glucose homeostasis are associated with specific structural features among adults without knee osteoarthritis: a cross-sectional study from the osteoarthritis initiative. - Stout, Alina C.; Barbe, Mary F.; Eaton, Charles B.; Amin, Mamta.; Al-Eid, Fatimah.; Price, Lori Lyn.; Lu, Bing.; Lo, Grace H.; Zhang, Ming.; Pang, Jincheng.; McAlindon, Timothy E.; Driban, Jeffrey B. (2018)
Background: Greater age and body mass index are strong risk factors for osteoarthritis (OA). Older and overweight individuals may be more susceptible to OA because these factors alter tissue turnover in menisci, articular cartilage, and bone via altered glucose homeostasis and inflammation. Understanding the role of inflammation and glucose homeostasis on structural features of early-stage OA may help identify therapeutic targets to delay or prevent the onset of OA among subsets of adults with these features. We examined if serum concentrations of glucose homeostasis (glucose, glycated serum protein [GSP]) or inflammation (C-reactive protein [CRP]) were associated with prevalent knee bone marrow lesions (BMLs) or effusion among adults without knee OA.; Keywords: Bone marrow lesions, Effusion, Magnetic resonance imaging, Osteoarthritis.; Springer Open.